2013
DOI: 10.1007/s00340-013-5340-6
|View full text |Cite
|
Sign up to set email alerts
|

Optical-feedback cavity-enhanced absorption spectroscopy with a quantum-cascade laser yields the lowest formaldehyde detection limit

Abstract: International audienceWe report on the first application of Optical Feedback-Cavity Enhanced Absorption Spectroscopy to formaldehyde trace gas analysis at mid-infrared wavelengths. A continuous-wave room-temperature, distributed-feedback quantum cascade laser emitting around 1,769 cm-1 has been successfully coupled to an optical cavity with finesse 10,000 in an OF-CEAS spectrometer operating on the ν2 fundamental absorption band of formaldehyde. This compact setup (easily transportable) is able to monitor H2CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…19 Gorrotxategi-Carbajo et al used optical feedback cavity enhanced spectroscopy to achieve an MDA of 5 × 10 −10 cm −1 in 1 s. 20 Of special interest is the external cavity quantum cascade laser (EC-QCL), which can tune over many microns (5-14 μm) allowing unprecedented spectral coverage. 21 Unfortunately, EC-QCLs capable of tuning over the widest spectral range also have a wide spectral bandwidth (∼0.5 cm −1 ), which makes them unsuitable for high resolution optical spectroscopy (e.g., single rotational-vibrational transitions of molecules with 2-5 atoms).…”
Section: 16-18mentioning
confidence: 99%
“…19 Gorrotxategi-Carbajo et al used optical feedback cavity enhanced spectroscopy to achieve an MDA of 5 × 10 −10 cm −1 in 1 s. 20 Of special interest is the external cavity quantum cascade laser (EC-QCL), which can tune over many microns (5-14 μm) allowing unprecedented spectral coverage. 21 Unfortunately, EC-QCLs capable of tuning over the widest spectral range also have a wide spectral bandwidth (∼0.5 cm −1 ), which makes them unsuitable for high resolution optical spectroscopy (e.g., single rotational-vibrational transitions of molecules with 2-5 atoms).…”
Section: 16-18mentioning
confidence: 99%
“…It has been demonstrated that this technique is compatible with different kinds of semiconductor lasers. Indeed, while OF-CEAS was previously developed in the NIR with distributed feedback telecom diode lasers (Morville et al, 2005;Kassi et al, 2006), it has been demonstrated that it is compatible with extended cavity diode lasers that operate in the visible (Courtillot et al, 2006;Horstjann et al, 2014) and with quantum cascade lasers (Maisons et al, 2010;Gorrotxategi-Carbajo et al, 2013) as well as more recently with interband cascade lasers (Manfred et al, 2015;Richard et al, 2016) in the mid-infrared region.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the OF-CEAS technique in the NIR led a private company (AP2E, Aix-en-Provence, France) to exploit the patent for commercially available analysers (namely Pro-CEAS). On the other hand, exploiting OF-CEAS in the MIR allows the reaching of sub-ppb levels for several species of interest in trace detection and ppm levels for isotopic ratio measurements (Maisons et al, 2010;Gorrotxategi-Carbajo et al, 2013;Manfred et al, 2016;Richard et al, 2016).…”
Section: Ventrillard Et Al: Comparison Of Of-ceas and Gcmentioning
confidence: 99%
“…Using this geometry, Maisons et al reported a minimum detectable absorption coefficient (α min ) of 3 × 10 −9 cm −1 for 1-s averaging measurements of N 2 O and CO 2 with a 4.46 µm QCL, while Hamilton et al went to longer wavelengths to probe CH 4 and N 2 O at 7.84 µm and achieved an α min of 5.5 × 10 −8 cm −1 for 1-s averaging [9,10]. Recently, Gorrotxategi-Carbajo et al [11] reported the best mid-infrared OF-CEAS sensitivity of 1.6 × 10 −9 cm −1 for a single scan (100 ms) probing formaldehyde with a 5.6 µm QCL.…”
Section: Introductionmentioning
confidence: 97%
“…Optical-feedback cavity-enhanced absorption spectroscopy (OF-CEAS) is a variant that uses the optical cavity to reduce the linewidth of the laser source emission and thereby increase lasercavity coupling [5][6][7][8][9][10][11][12]. In essence, the resonant cavity field retraces back to the laser facet and acts as an external source of injection seeding.…”
Section: Introductionmentioning
confidence: 99%